2018
DOI: 10.1007/s00204-018-2305-x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride induces apoptosis and autophagy through the IL-17 signaling pathway in mice hepatocytes

Abstract: Previous studies have reported that excessive fluoride exposure induced liver damage. However, the underlying mechanism of fluoride-induced hepatic toxicity is still unclear. Hence, this study was aimed to evaluate the fluoride-induced apoptosis, autophagy, and IL-17 signaling pathway-related genes to explore the possible mechanisms of NaF-induced liver injury in mice. For this, 48 male mice were allotted randomly to four groups, treated with deionized water, 25, 50, 100 mg/L NaF for 150 days continuously. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…Earlier studies revealed that the height and weight of children in F-contaminated areas were signi cantly lower than those in normal areas [14]. Recent works using animal models reported that rats or mice exposed to super uous F could experience a signi cant reduction in weight and organ coe cient of liver [15,16]. This corroborates with our results, which shows that the weight gain of mice exposed to 50 mg/L NaF for 90 days signi cantly differs from the control group, indicating that excessive F exposure causes an adverse effect on the growth performance of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies revealed that the height and weight of children in F-contaminated areas were signi cantly lower than those in normal areas [14]. Recent works using animal models reported that rats or mice exposed to super uous F could experience a signi cant reduction in weight and organ coe cient of liver [15,16]. This corroborates with our results, which shows that the weight gain of mice exposed to 50 mg/L NaF for 90 days signi cantly differs from the control group, indicating that excessive F exposure causes an adverse effect on the growth performance of mice.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that HIF-1α signaling pathway plays an important role in the regulation of TNF-α-induced proliferation and metastasis of A549 cells in NSCLC [59]. In addition, there are five other pathways: p53 signaling pathway [60,61], cellcycle, ErbB signaling pathway [62], IL-17 signaling pathway [51,52,63,64], small cell lung cancer, vascular endothelial growth factor signaling pathway [65,66]. All of them are closely related to the occurrence of lung cancer, apoptosis of tumor cells, and immune function.…”
Section: Pathway Analysis Of Xqd Acting On Lc Therapeutic Targetsmentioning
confidence: 91%
“…Interleukin-17 in the IL-17 signaling pathway plays a crucial role in acute and chronic inflammatory responses (Zhao, Li, Li, Wang, Manthari, & Wang, 2018). Interleukin-17 in the IL-17 signaling pathway plays a crucial role in acute and chronic inflammatory responses (Zhao, Li, Li, Wang, Manthari, & Wang, 2018).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…additional evidence that GABAergic dysfunction may lead to mood and cognitive symptoms of MDD. Interleukin-17 in the IL-17 signaling pathway plays a crucial role in acute and chronic inflammatory responses (Zhao, Li, Li, Wang, Manthari, & Wang, 2018). Neuroendocrine and immune system interactions play an important role in stress response (Ashley & Demas, 2017;Dantzer, 2018).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%